コウクウキ トウサイ デンパ ヒョウアツケイ ニ ヨル シラセ ヒョウガ オヨビ ソノ ジョウリュウ イキ ノ ヒョウゲン ト キバン チケイ チョウサ - 和田, 誠; ワダ, マコト; 前, 晋爾; マエ, シンジ; Wada, Makoto; Mae, Shinji (1981)
P(論文) 1980年1月29日に, 第21次南極地域観測隊が昭和基地に搬入, 飛行を実施していたピラタスポーター機に電波氷厚計を搭載し, 白瀬氷河およびその上流域で氷厚および基盤地形の調査を行った。使用周波数は179MHz, ピラタスポーター機の翼につけた三素子八木アンテナを使い送受信を行った。記録方式としては, 反射エコー強度をオシロスコープ輝度に変換し連続的に反射エコーを記録するシステムと, 飛行中2.5分ごとにAスコープ記録をとるシステムと2方式を採用した。なお, 今回使用した電波氷厚計の場合2000m以上の氷厚では, 電波の減衰により, 岩盤からの反射エコーはとらえることができなかった。測定結果から, 白瀬氷河下流域ではクレバスによるラジオ波散乱のため, 明らかな岩盤からの反射は記録されず, 白瀬氷河B地点(70°20′S, 39°20′E)から約30km上流部まで基盤は海面より高いところにあることがわかった。また, B地点から上流50kmまでは, 基盤地形は複雑であるが, それより上流部にはさほど複雑な地形はみられない。従前のCルートと交わっている飛行経路上の点(C94,C98)での氷厚は約1600mで, 以前に地上から測られた電波氷厚の値に一致する。 Airborne radio echo sounding carried out on the Shirase Glacier and its drainage basin in January 1980 is described. The new sounder (NIPR-A) was operated at 179 MHz on board a Pilatus Porter PC-6. Analysis of the continuous records of the sounding gave the bedrock topography along the flow line as well as in several cross sections of the downstream part of the glacier. The intense echo caused by the crevasses in the downstream masked that from the bed and so the depth and profile of the bedrock were obscured. In the lower part near point B (70°20′S, 39°20′E), the bedrock was partly below sea level. The bedrock topography 50km upstream from B is complicated compared with that of the upper reaches of the Shirase Glacier drainage basin. The thickness of ice on the former C route taken by the traverse party in 1974 (C94,98) coincided well with the present results. departmental bulletin paper